Comparative Effects of Compound Enzyme and Antibiotics on Growth Performance, Nutrient Digestibility, Blood Biochemical Index, and Intestinal Health in Weaned Pigs - Li, Zhiqing; Tang, Lizi; Liu, Nian; Zhang, Fan; Liu, Xiang; Jiang, Qian; Chen, Jiashun; Ma, Xiaokang (Frontiers in Microbiology, 2021)
This experiment aims to explore the effects of complex enzyme preparation substituting chlortetracycline in weaned piglets. A total of twenty-four 28-day-old ‘Duroc × Landrace × Yorkshire’ weaned piglets with an average initial weight of 7.25 ± 0.25 kg were randomly divided into three groups according to their body weight, with eight replicates in each group and one pig in each replicate. The three dietary treatments were basal diet (CON), basal diet + 1,000 mg/kg complex enzyme preparation (cellulase 4, 000 IU/g, α-amylase 1,000 IU/g, β-glucanase 150 IU/g and neutral protease 3, 000 IU/g, CE) and basal diet + 75 mg/kg chlortetracycline (CTC). The animal experiment lasted for 28 days and was divided into two stages: the early stage (1 ~ 14 days) and the late stage (15 ~ 28 days). The results showed that: (1) Compared with the CON, the CE significantly increased the average daily gain of weaned piglets during the early and whole period of experiment (P < 0.05) (2) Compared with the CON, the apparent total tract digestibility of ADF and NDF was significantly increased in pigs fed CE diet in the early and late stages of experiment (P < 0.05). (3) Compared with the CON, the concentrations of serum immunoglobulin A and superoxide dismutase in weaned piglets were significantly increased in CE group in the early stage of the experiment (P < 0.05). The content of serum malondialdehyde in the CE group showed a downward trend (P < 0.10) compared with the CON group during the whole experiment period. (4) Compared with the CON group, the acetic acid, propionic acid and total volatile fatty acids contents in cecum and colon segments elevated in the CE group (P < 0.05). (5) Compared with the CON group, the villus height of duodenum and jejunum and the ratio of villus height to recess depth of ileum were increased in the CE group (P < 0.05). (6) Compared with the CON group, the abundance of Lactobacillus significantly increased (P < 0.01). In conclusion, complex enzyme preparation instead of chlortetracycline can contribute to the promoted growth performance of piglets.